2019
DOI: 10.1186/s40942-018-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

Release of silicone oil droplets from syringes

Abstract: BackgroundIntravitreal silicone oil droplets have been found in the vitreous. The aim of this study is to compare the rates of silicone oil released by different brands of commonly used syringes for intravitreal injection after agitation by flicking.MethodsThree models of two brands of syringes were analyzed for their rates of silicone oil release: Saldanha Rodrigues (SR) 1 mL insulin syringe (SR, Brazil, syringe 1), Becton–Dickinson (BD) Plastipak 1 mL insulin syringe (Brazil, syringe 2), and BD Safety-Glide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
2
29
1
Order By: Relevance
“…In fact, although it is not possible to state which syringe was used for each patient, the syringe models available in the last 5 years at the clinical setting where these patients were treated were Becton–Dickinson (BD) Plastipak 1 mL (Becton, Dickinson [BD] and Co., Curitiba, Brazil), SR 1 mL and BD SafetyGlide 1 mL (BD and Co., Holdrege, NE). Both the SR and the BD SafetyGlide syringes have been shown to release silicone oil droplets, especially after agitation [16]. Coincidently, the retina specialist responsible for those injections in this study used to flick the syringe until a few months prior to the data collection, which we believe promotes a greater detachment of oil from the inner surface of the syringes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In fact, although it is not possible to state which syringe was used for each patient, the syringe models available in the last 5 years at the clinical setting where these patients were treated were Becton–Dickinson (BD) Plastipak 1 mL (Becton, Dickinson [BD] and Co., Curitiba, Brazil), SR 1 mL and BD SafetyGlide 1 mL (BD and Co., Holdrege, NE). Both the SR and the BD SafetyGlide syringes have been shown to release silicone oil droplets, especially after agitation [16]. Coincidently, the retina specialist responsible for those injections in this study used to flick the syringe until a few months prior to the data collection, which we believe promotes a greater detachment of oil from the inner surface of the syringes.…”
Section: Discussionmentioning
confidence: 85%
“…A case–control analysis reinforced the suspicion that a new syringe introduced at the injection facility had an association with the cases with inflammation [14]. Thereafter, our group carried out experimental studies that showed that silicone oil might be released by syringes under steady-state conditions, but more commonly with agitation by flicking [1618]. Additionally, needles have been shown to be coated with silicone oil [19].…”
Section: Discussionmentioning
confidence: 99%
“…The syringes used for this study (Beckton-Dickinson, BD Safety-Glide™ 1 mL insulin syringe with BD Ultra-Fine™ needle) are lubricated with silicone oil and are known to release oil droplets. 36 …”
Section: Resultsmentioning
confidence: 99%
“…49 Several studies have shown that flicking or agitation of the syringes results in a high amount of silicone oil droplets inside the syringes. 37,50 The authors carried out further investigations on the particle count in two bevacizumab syringes filled by different compounding pharmacies (University and External), as well as the aflibercept vial and the ranibizumab ready-to -use syringe available in Germany. The transport route was also taken into account.…”
Section: Silicone Oil Droplets and Protein Aggregatesmentioning
confidence: 99%